ICT and economic growth: Comparing developing, emerging and developed countries - Thomas Niebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper analyzes the impact of information and communication technologies (ICT) on economic growth in developing, emerging and developed countries. It is based on a sample of 59 countries for the period 1995 to 2010. Various panel data regressions confirm the positive relationship between ICT capital and GDP growth. The regressions for the subsamples of developing, emerging and developed countries do not reveal statistically significant differences of the output elasticity of ICT between these three country groups.
Keywords: E22; J24; O47; 330; ICT; Economic Growth